5X + 5 = 14 + 2X
subtract 2X from both sides
3X + 5 = 14
subtract 5 from both sides
3X = 9
divide both sides integers by 3
(3/3)X = 9/3
X = 3
=======check in original equation
5(3) + 5 = 14 + 2(3)
15 + 5 = 14 + 6
20 = 20
=======checks
2x+a=p 2x=p-a x=.5p-.5a
-2x+14=20 x=-3
4x + 2 + 2x - 2x = 14 4x = 14 - 2 4x = 12 x = 3
many solutions
2x + 2x + 146 + 26 = 172 4x + 172 = 172 4x = 0 x = 0
4x + 3 = -3 + 2x + 14 2x + 3 = -3 +14 2x + 3 = 11 2x = 8 x=4
2x+3 = -11 2x = -11-3 2x = -14 x = -7
-2x+14=20 -2x=20-14 -2x=6 -2x/-2=6/-2 x=-3
2x+a=p 2x=p-a x=.5p-.5a
y= -2x
If -2x +14 = 0, -2x = -14, or x = 7.
balance the equation 3x-x=20-6 3x-x=2x 20-6=14 2x=14 x=7
3
-2x+14=20 x=-3
8
4x + 2 + 2x - 2x = 14 4x = 14 - 2 4x = 12 x = 3
You do 6+2x=-14 Then you do 6-6+2x=-14-6 that way u can get 2x all by itself Ok now you have 2x=-20 now Divide both sides by 2 That gives you x=-10 I hope that helps!